The Effectiveness of Loan Interest Rate, Money Supply, Exchange Rate, Investment, and Inflation on Economic Growth: A Comparative Study Between Pre- and Post-2008 Global Crisis Periods - Putih Nurmala Sari; Ghozali Maski (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to analyze the effectiveness of Bank Indonesia’s monetary policy, represented by loan interest rate, money supply, exchange rate, investment, and inflation, on Indonesia’s economic growth before and after the 2008 global financial crisis. The methods used are the Domowitz-El Badawi Error Correction Model (ECM) and Chow test to examine structural differences between the two periods. The findings reveal that the selected variables are not statistically significant in affecting economic growth during both periods, except for the exchange rate which has a significant negative effect in the pre-crisis period. The Chow test confirms the presence of a significant structural shift, indicating a change in monetary policy effectiveness after the crisis. These results provide empirical insights and practical implications for formulating more adaptive monetary policies in post-crisis economic conditions.